Temporal and spatial pattern of wildlife attacks on human in Chitwan National Park, Nepal - Kandel, Saroj; Silwal, Thakur; Yadav, Shailendra Kumar; Dhakal, Sandesh (Nepalese Journal of Zoology, 2023)
Wildlife attacks on humans pose a critical challenge to wildlife conservation. Comprehensive information about the conflict cases can be vital for effective wildlife management and conservation. In this study, we assessed the temporal and spatial patterns of wildlife attacks on humans in Chitwan National Park between January 2009 to December 2020 by using the annual reports published by the park. Our analysis revealed that out of the nine-wildlife species involved in conflicts, rhinos, elephants, tigers, sloth bears, and wild boars had significantly higher involvement in conflicts with humans. The findings showed that an average of 42 annual attacks and 10 human fatalities cases were reported annually. Of these species, rhinos exhibited the most frequent involvement in conflicts (38%), while elephants were found to be the most lethal species, causing an average of 3.75 human fatalities per year. The trend line indicated a marginal increase in wildlife attacks on humans by 3.97 per year (adjusted R2=0.36). Our study further revealed that wildlife attacks were mostly concentrated in the winter season (χ2=1.088, df=3, p<0.05), with elephant, rhino, and tiger attacks predominantly occurring in the proximity of human settlements. To evaluate the risk factors of human deaths due to wildlife attacks, we utilized logistic regression analysis and found elephant attacks were associated with the highest probability of causing human fatalities (odd ratio=15.2, p<0.05), followed by tiger attacks (odd ratio=8.41, p<0.05). The study revealed an increasing trend in attacks, predominantly occurring in winter and near human settlements. Elephants and tigers are identified as the highest risk factors for human fatalities. Understanding these patterns is crucial for effective wildlife management and conservation efforts.